2016
DOI: 10.18632/oncotarget.11273
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonists promote differentiation of cancer stem cells by restraining YAP transcriptional activity

Abstract: Osteosarcoma (OS) is a highly aggressive pediatric bone cancer in which most tumor cells remain immature and fail to differentiate into bone-forming osteoblasts. However, OS cells readily respond to adipogenic stimuli suggesting they retain mesenchymal stem cell-like properties. Here we demonstrate that nuclear receptor PPARγ agonists such as the anti-diabetic, thiazolidinedione (TZD) drugs induce growth arrest and cause adipogenic differentiation in human, mouse and canine OS cells as well as in tumors in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…Previous investigation in mesenchymal stem cells has shown that TAZ negatively modulates adipogenesis by repressing PPARG . Therefore, the regulation of YAP1 on adipogenesis may be related to the activation of PPARG . IBMX is an inducer of adipogenesis that can elevate cyclic adenosine monophosphate (cAMP) content to activate PPARG expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigation in mesenchymal stem cells has shown that TAZ negatively modulates adipogenesis by repressing PPARG . Therefore, the regulation of YAP1 on adipogenesis may be related to the activation of PPARG . IBMX is an inducer of adipogenesis that can elevate cyclic adenosine monophosphate (cAMP) content to activate PPARG expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the group of Guan demonstrated that YAP plays a crucial role in protein kinase A (PKA)‐induced adipocyte differentiation . Intriguingly, recent study in osteosarcoma cells and mice implanted with osteosarcoma cells found that PPARG agonists can reduce the nuclear localization of YAP1 and promote adipogenesis in the tumors . Similarly, knocking out Yap in osteoblast‐lineage cells suppresses cell proliferation and promotes adipocyte formation .…”
Section: Introductionmentioning
confidence: 99%
“…386 PPARγ activation also prevents cell spheroid formation and stem cell-like properties in bladder CSCs and induces adipocyte differentiation and β-catenin degradation in adipose tissues. 387 Furthermore, expression of PPARγ restrains YAP transcriptional activity to induce differentiation in osteosarcoma stem cells 388 and melanoma cells. 389 The PPARγ/NF-κB pathway promotes M2 polarization of macrophages to prevent cell death in ovarian CSCs 4.390 PPARγ activation promotes expression of its target gene PTEN to inhibit PI3K/Akt/ mTOR signaling, which stunts self-renewal, tumorigenicity, and metastasis in cervical CSCs, glioblastoma stem cells, and liver CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…It elicits terminal granulocytic differentiation in the leukemia cells by impairing transcriptional repression of genes necessary for differentiation (12). Differentiation therapy has the potential to be beneficial for cancer resistant to conventional agents, but limited evidence is available at present regarding its applicability to solid tumors (13,14). We have therefore now pursued the identification of a chemoresistant subpopulation of OSi cells and found that, in contrast to AX cells, AO cells are highly resistant to doxorubicin.…”
Section: Introductionmentioning
confidence: 99%